IFI44 is an immune evasion biomarker for SARS-CoV-2 and Staphylococcus aureus infection in patients with RA - Zheng, Qingcong; Wang, Du; Lin, Rongjie; Lv, Qi; Wang, Wanming (Frontiers in Immunology, 2022)
Background: SARS-CoV-2 caused a global pandemic of severe coronavirus disease 2019 (COVID-19). Staphylococcus aureus is one of the most common pathogenic bacteria in humans, Rheumatoid arthritis (RA) is among the most prevalent autoimmune conditions. The purpose of this study is to investigate the biomarkers and disease targets between RA and SARS-CoV-2 and S. aureus infections using bioinformatics analysis, to search for the molecular mechanisms of SARS-CoV-2 and S. aureus immune escape and potential drug targets in the RA population. Methods: The RA dataset (GSE93272) and the SAB dataset (GSE33341) were used to obtain differentially expressed gene sets, respectively, and the common DEGs were determined through the intersection. Functional enrichment analysis utilizing GO, KEGG, and ClueGO methods. The PPI network was created utilizing the STRING database. The top 10 hub genes were intersected with the SARS-CoV-2 gene pool to identify 5 hub genes shared by RA, COVID-19, and SAB. The hub gene was verified utilizing GSE17755, GSE55235, and GSE13670,. CIBERSORT was applied to examine immune cell infiltration and the link between the hub gene and immune cells. Results: IFI44, OAS1, IFI44L, ISG15, and HERC5 are the five hub genes shared by RA, COVID-19, and SAB. The pathways are primarily enriched for response to viral and bacterial infections. The TF-hub gene network and miRNA-hub gene network identified YY1 as a key TF and hsa-mir-1-3p and hsa-mir-146a-5p as two important miRNAs related to IFI44. IFI44 was identified as a hub gene by validating GSE17755, GSE55235, and GSE13670. Immune cell infiltration analysis showed a strong positive correlation between Dendritic cells activated and IFI44 expression. Conclusions: IFI144 was discovered as a shared biomarker and disease target for RA, COVID-19, and SAB by this study. IFI44 negatively regulates the IFN signaling pathway to promote viral replication and bacterial proliferation and is an important molecular target for SARS-CoV-2 and S. aureus immune escape in RA. Dendritic cells play an important role in this process.1,25 Dihydroxy vitamin D3 may be an important therapeutic agent in treating RA with SARS-CoV-2 and S.aureus infections.